Nathan for You and the New Sincerity aesthetic. Issue 4 (1st October 2020) - Thompson, Lucas
ABSTRACT: This article argues that Comedy Central's Nathan For You enacts a sophisticated critique of reality television and offers a different way of capturing 'reality' on the small screen. By exaggerating the format's countless constraints, Nathan for You discovers a way to create real and moving drama from reality television conventions. Using examples taken from across the series, the article argues that the show exemplifies the New Sincerity aesthetic that scholars in numerous other fields have found across contemporary US culture. What Fielder's project ultimately reveals is that the most exaggerated and grotesque forms of reality-television manipulation can paradoxically open up spaces of sincere communication and feeling. The article also explores many of the formal and stylistic devices that Fielder uses across the series, building a case for a reevaluation of the series.